Psychological Well-Being, Cognitive Functioning, and Quality of Life in 205 Adolescent and Young Adult Childhood Cancer Survivors Compared to Healthy Peers - Tremolada, Marta; Taverna, Livia; Bonichini, Sabrina; Pillon, Marta; Biffi, Alessandra (Frontiers in Psychology, 2022)
The majority of the studies underlined how adolescent and young adult (AYA) cancer survivors had no significant differences in their well-being and quality of life compared with a control group of healthy counterparts, although French et al. (2013) found less years of education among them. The present study aimed at comparing AYA and a control group of peers who had no history of serious illness, in terms of well-being, cognitive functioning, and perceptions of life. Participants in this study were 205 AYA cancer survivors, 126 males, off therapy from a mean of 10.87 years (SD=4.91), with a mean age of 18.96 (SD = 3.08), recruited during follow-up visits and 205 healthy counterparts, matched for age and gender. They all completed self-report questionnaires: Ladder of Life, BSI-18 and scale of Cognitive problems. Paired t test evidenced significant differences between survivors (Mean=6.19; SD = 2.07) and controls (Mean = 6.88; SD = 2.02) in perceptions of quality of life regarding 5 years before the current time (t(204) = -3.39; p = 0.001), with a lower level for survivors. Hierarchical regression (R2 = 0.05, p = 0.04) identified a shorter time since the completion of treatment ( = 0.18, p = 0.03) and a trend of stem cell transplantation experience ( = -0.11, p = 0.06) as factors associated with negative perception of precedent quality of life. The AYA cancer survivors reported lower cognitive difficulties (Mean = 1.46) than controls (Mean=1.56) (t(204) = -3.41; p = 0.001): in memory (Mean clinical = 1.32 vs Mean control = 1.50) (t(204) = -4.52; p = 0.001), in concentration (Meanclinical = 1.36 vs Mean control = 1.54) (t(204) = -4.66; p = 0.001) and in mental organization skills (Meanclinical = 1.47 vs Mean control = 1.56) (t(204) = -2.56; p = 0.01), even if they had a lower educational attainment (X2(9) = 131.28; p = 0.001). They showed similar satisfaction with their psychological well-being and their lives as healthy counterparts, except for past life perceptions associated with the cancer period. Important recommendations for future research and clinical suggestions could be given.